Candida, the opportunistic human pathogen - Sakina, Shahabudin; Nina Suhaity, Azmi (Trans Tech Publications, 2020)
Candida species are known human pathogens that have caused high morbidity and mortality among affected individuals. Candida albicans can switch forms from yeast to hyphae, in which both forms are virulent. Due to its commensal status in normal human microflora, C. albicans poses a virtual threat to humankind because of their dimorphism ability under opportunistic environmental conditions. Because of the increased usage of prophylactic antifungal agents in the treatment of candidiasis, reports of Candida species developing antifungal resistance are increasing. Recent observations of cross-reaction between different classes of antifungal drugs that could yield multidrug-resistant pathogenic Candida species are concerns that need to be urgently addressed.